2012
DOI: 10.18806/tesl.v29i2.1104
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role for Role-Playing Pedagogy

Abstract: This article draws from practitioners’ experience and from scholarship in a variety of disciplines to construct a rationale for incorporating what we call “critical roleplay” in the English-for-academic-purposes (EAP) classroom. We discuss the historical significance of role-play in TESOL and explore why this type of pedagogy has become less prominent in scholarship from recent decades. We argue for a new direction in role-play pedagogy that foregrounds critical thinking as essential to academic literacy. We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 20 publications
(13 reference statements)
0
30
0
1
Order By: Relevance
“…Additionally, role-playing was used with English language learners, where teachers used role-playing in an attempt to move from a prescribed dialogue to an improvisational one. In this context, Shapiro and Leopold (2012) suggested that implementing role-playing in a classroom provides a "space between practice and play [which] is a fertile ground for cognitive and linguistic growth" (p. 128).…”
Section: On Role-playingmentioning
confidence: 99%
“…Additionally, role-playing was used with English language learners, where teachers used role-playing in an attempt to move from a prescribed dialogue to an improvisational one. In this context, Shapiro and Leopold (2012) suggested that implementing role-playing in a classroom provides a "space between practice and play [which] is a fertile ground for cognitive and linguistic growth" (p. 128).…”
Section: On Role-playingmentioning
confidence: 99%
“…Additionally, role-playing was used with English language learners, where teachers used role-playing in an attempt to move from a prescribed dialogue to an improvisational one. In this context, Shapiro and Leopold (2012) Abstract Equity in education has been a concern of almost all countries, whether developed, transitional, or in the progress of developing. It is believed that unequal education implies that human potential is being wasted.…”
Section: Chapter 15mentioning
confidence: 99%
“…The apparent dynamism of this particular dramatic activity was that it allowed for a range of interpretations and allowed students to share their own stories. However, in keeping with the critical nature of the investigation, this study also raises questions about what kinds of activities might teach what Shapiro and Leopold (2012) call critical role play, where students become more aware of linguistic structures and intellectual arguments by embodying voices and perspectives that are different from habitual self-expression or their experiences. Along similar lines, the statue activity did allow students to take greater artistic license with language; furthermore, it is worth considering whether students would be as successful with dramatic activities that required more technical vocabulary and register (such as a scientist introducing an invention or hypothesis).…”
Section: Conclusion: Academic Language and The Potentials Of Embodiedmentioning
confidence: 99%